Scope and Importance of Environmental Studies: Exploring the Interdisciplinary Nature of Environmental Studies (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The science of Environment studies is amulti-disciplinary science because it comprises various branches of studieslike chemistry, physics, medical science, life science, agriculture,public   health, sanitary engineeringetc.  It is the science of  physical phenomena  in the  environment. It studies of the  sources, reactions, transport,  effect and  fate  of physical a biological species in  the  air, water and  soil  and the  effect  of from human activity upon these.